Efficiency improvement of cellulose derivative nanocomposite using titanium dioxide nanoparticles - De Moura, Márcia R. [UNESP]; Zucolotto, Valtencir; Aouada, Fauze A. [UNESP]; Mattoso, Luiz H. C. (American Scientific Publishers, 2017)
TiO2 nanoparticles were incorporated into hydroxypropyl methylcellulose (HPMC) nanocomposites films. The nanocomposites were investigated in relation to their structural, mechanical, and surface properties using scanning electron microscopy (SEM). The water solubility of the films showed a small decrease with respect to the nanocomposites films' content of the TiO2 nanoparticles. Incorporation of TiO2 nanoparticles in the films improved their mechanical and barrier properties significantly. SEM images showed that the lower concentration of nanoparticles were better dispersed in the nanocomposite matrix. The disk diffusion studies revealed a great bactericidal effectiveness for nanocomposite films containing smaller concentration of particles. In general, it was observed that the incorporation of the nanoparticles positively affected the structural properties and enhanced the antibacterial applications of the nanocomposites.
Keywords: Biomaterial; Mechanical properties; Nano-structures; Polymer-matrix composites